Simulative analysis of storm surge towards a rational vertical siting of an open pier in Jagna, Bohol - Cuarto, Cindy G.
Ports are vital in the economy ofthe country. In the case of Jagna Seaport, Bohol, it is the gateway portal to Mindanao. Being part of the Strong Republic Nautical Highway, large vessels and cargo ships dock at this port. Since there are many physical processes that take place in the ocean and nearshore areas, the port is subjected to different marine loadings. The selection of proper horizontal and vertical siting is thus very crucial. Given that an appropriate site location has been determined, it follows that a proper vertical siting of the port structure is imperative. Vertical siting consists of astronomical tide, storm surge, local wave height and wave-structure interactions. This study focuses only on the storm surge component of the vertical siting of the port. Storm surge is the rise of water level caused by a storm due to wind shear stress and pressure drop. Being an interior port along an irregular coastline, Jagna Port's storm surge hazard can be studied via numerical modeling. This study carried out numerical simulations of historical typhoons based on the Delft3D model. The typhoon events simulated are Jangmi/Seniang (201 4), Bopha/Pablo (2012) and Washi/Sendong (2011). It was found that the maximum historical storm surge is 0.62 m. However, the highest storm tide level is found to be Mean Sea Level + 0.81 m. Based on this and the pier's characteristics, the maximum headroom for wave effects is 2.39 m.